(untitled) (Revista de Ensino em Artes, Moda e Design, 2022)
The objective is to examine recent productions by Brazilian multiartist Lyz Parayzo that involve jewelry and other wearable objects. The specific focus of the analysis is the series of flyers entitled “Putinha Terrorista” (2016-2018). The texts and photographic images included in the flyers are analyzed, especially when wearable objects created by the artist herself appear as costume elements. The analysis highlights the way in which Lyz Parayzo makes intense use of Fashion codes to produce an activist art in favor of the transvestite/transgender population. The contribution of the study stems from the fact that, as far as we could evaluate, no research has analyzed the work of Lyz Parayzo specifically from the Fashion perspective.